DNASE1L3 inhibits proliferation, invasion and metastasis of hepatocellular carcinoma by interacting with β‐catenin to promote its ubiquitin degradation pathway. Issue 9 (24th June 2022) - Li, Bo; Ge, Yu‐Zhen; Yan, Wei‐Wei; Gong, Bin; Cao, Kun; Zhao, Rui; Li, Chao; Zhang, Ye‐Wei; Jiang, Yi‐Heng; Zuo, Shi
Abstract: As a member of the deoxyribonuclease 1 family, DNASE1L3 plays a significant role both inside and outside the cell. However, the role of DNASE1L3 in hepatocellular carcinoma (HCC) and its molecular basis remains to be further investigated. In this study, we report that DNASE1L3 is downregulated in clinical HCC samples and evaluate the relationship between its expression and HCC clinical features. In vivo and in vitro experiments showed that DNASE1L3 negatively regulates the proliferation, invasion and metastasis of HCC cells. Mechanistic studies showed that DNASE1L3 recruits components of the cytoplasmic β‐catenin destruction complex (GSK‐3β and Axin), promotes the ubiquitination degradation of β‐catenin, and inhibits its nuclear transfer, thus, decreasing c‐Myc, P21 and P27 level. Ultimately, cell cycle and EMT signals are restrained. In general, this study provides new insight into the mechanism for HCC and suggests that DNASE1L3 can become a considerable target for HCC. Abstract : Decreased expression of DNASE1L3 is associated with poor prognosis in patients with HCC DNASE1L3 inhibits the proliferation and cell cycle of HCC cells in vitro and promotes the invasion and metastasis of HCC cells DNASE1L3 inhibits the tumorigenicity and metastasis of HCC cells in vivo DNASE1L3 interacts with β‐catenin and promotes its binding to the β‐catenin destroying complex DNASE1L3 interacts with P21 and stabilizes P21 by mediating the deubiquitin activity